Perancangan Antarmuka Pengguna (UI/UX) Aplikasi Fun Run Menggunakan Metode Design Thinking - Iswanti, Siti; Muthi’ah Sari, Khofifah Indah; Oktaviani, Adelia (PT Jurnal Cendekia Indonesia, 2025)
Digital technology advancement has spurred sports applications promoting healthy lifestyles, with fun run events gaining popularity as community-based activities. However, participant registration and information management remain challenging due to inadequate digital integration. This research designs the FunRun application's UI/UX using Design Thinking's user-centered methodology through five stages: Empathize, Define, Ideate, Prototype, and Test. Data collection involved interviews and observations with prospective participants and organizers to identify user needs and pain points. The outcome is an interactive Figma prototype featuring five core screens: home, registration, history, track and digital certificate. Usability testing via System Usability Scale (SUS) with 15 respondents achieved an average score of 87 (